PKM SEMINAR CRITICAL THINKING : PENTINGNYA BERFIKIR KRITIS SEBAGAI SEORANG PELAJAR DI SMA TERPADU MATHLA’UL ANWAR - Miftahul Huda; Intan Sari; Sarmila Sarmila; Rachmawan Pramuliatama; Eneng Rustia; Rani Septiani Sukandar (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
The signs of people who have skill of critical thinking are usually marked by the emergence of any questions in their effort to obtain information related to a phenomenon that appears and seek a solution. Some of the characteristics of person who thinks critically tend to have a mindset of perspective, objective, creative, sensitive, diligent and have a high curiosity. As a teenager going to growing up, high school students are required to be able to determine good or bad for everything. In addition, having skills of critical thinking can also help students in conducting research, making effective decisions and having high self-confidence. To gain all of that, then the provision of critical thinking skills is considered necessary. Critical thinking is a skill that can be trained. Based on this, the purpose of this dedication activity is to carry out a colloquium activity to provide knowledge to students about critical thinking and how to train it. Colloquium activity give a way to practice skill of critical thinking by asking any questions frequently and being a good listener. Even someone who si slow in thinking can also having skill of critical thinking by doing the exercise